2010
DOI: 10.1111/j.1463-5224.2010.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical KINOSTAT™ ameliorates the clinical development and progression of cataracts in dogs with diabetes mellitus

Abstract: Objective To determine whether topical administration of the aldose reductase inhibitor KinostatÔ can ameliorate the onset or progression of cataracts in dogs with naturally occurring diabetes mellitus (DM). Materials and Methods A randomized, prospective, double-masked placebo control pilot study was conducted with 40 dogs newly diagnosed with DM with no or minimal lens changes. Twenty-eight dogs received KinostatÔ and 12 dogs received placebo. Procedures Owners administered the agent into both eyes three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…In addition, strategies using inhibitors have provided numerous pieces of evidence to implicate AKR1B1 in diabetic cataract in various experimental models. Thus, topical administration of an aldose reductase inhibitor delays the development of cataracts in diabetic dogs (Kador et al, 2010), and oral treatment with another inhibitor prevents their progression in rats (Kawakubo et al, 2012). The results presented herein show that both PGA 1 and PGE 1 reduce the formation of sorbitol in isolated rat lenses exposed to high glucose, thus opening the way for in vivo studies.…”
Section: Prostaglandins Inhibit Aldose Reductasementioning
confidence: 76%
“…In addition, strategies using inhibitors have provided numerous pieces of evidence to implicate AKR1B1 in diabetic cataract in various experimental models. Thus, topical administration of an aldose reductase inhibitor delays the development of cataracts in diabetic dogs (Kador et al, 2010), and oral treatment with another inhibitor prevents their progression in rats (Kawakubo et al, 2012). The results presented herein show that both PGA 1 and PGE 1 reduce the formation of sorbitol in isolated rat lenses exposed to high glucose, thus opening the way for in vivo studies.…”
Section: Prostaglandins Inhibit Aldose Reductasementioning
confidence: 76%
“…Kinoshita was the first to demonstrate the hyperosmotic effects of intracellular sorbitol or galactitol accumulation and to postulate that the resulting cellular swelling can lead to increased membrane permeability and a series of complex biochemical changes associated with sugar cataract formation (Kador and Kinoshita, 1984; Kinoshita, 1974; Kinoshita et al, 1979). The central role of AR in sugar cataract formation has been confirmed by the ability of ARIs to prevent sugar cataract formation in diabetic or galactosemic animals (Kador and Kinoshita, 1984; Kador et al, 2010b; Kinoshita, 1974; Mizuno et al, 1990). …”
Section: Discussionmentioning
confidence: 95%
“…These anti-aggregation or chaperone approaches might be combined with inhibitors of the UPR to help mitigate the effects of any unstable protein resistant to small molecule chaperones. In addition, it has been demonstrated that topical administration of an aldose reductase inhibitor (Kinostat) delays onset and progression of cataracts in dogs with naturally occurring diabetes mellitus (Kador et al, 2010). While these preliminary results with small molecules are promising, it is noteworthy that several other animal-model studies of small molecules with anti-oxidant and/or anti-aggregation (chaperone) properties including; plant-flavonoids, aspirin, N-acetyl carnosine, curcumin, caffeine, and multivitamins have not resulted in universal clinical approval for use as anti-cataract drugs in humans.…”
Section: Age Related Cataractmentioning
confidence: 99%